Focal and Generalized Seizure Characteristics in Uremic and Hepatic Metabolic Encephalopathy : A Systematic Review of Randomized Controlled Trials and Primary Studies - David William Brian Iskandar (The Indonesian Journal of General Medicine, 2026)
Introduction: Metabolic encephalopathy arising from uremic and hepatic dysfunction represents a significant neurological emergency, manifesting across a spectrum from subtle cognitive impairment to overt convulsive status epilepticus. Seizures in this context are mechanistically distinct from idiopathic epilepsy, driven by accumulation of uremic toxins, hyperammonemia, astrocytic edema, disturbances in neurotransmission, and blood-brain barrier dysfunction. Despite the clinical importance of recognizing focal versus generalized seizure characteristics in these two paradigmatic forms of metabolic encephalopathy, a comprehensive synthesis of primary study evidence remains lacking. This systematic review aimed to characterize and compare focal and generalized seizure manifestations in uremic encephalopathy (UE) and hepatic encephalopathy (HE), evaluate EEG patterns, neuroimaging correlates, and clinical outcomes. Methods: The study strictly adhered to the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020 guidelines. Eligible studies included randomized controlled trials, cohort studies, case-control studies, cross-sectional studies, and observational studies reporting seizure characteristics in human subjects with confirmed uremic or hepatic metabolic encephalopathy. Risk of bias was assessed using the Newcastle-Ottawa Scale and Joanna Briggs Institute tools. Results: Fifteen primary studies (cumulative n >1,900,000 patients) were included. Seizures occurred in approximately 10% of patients with end-stage kidney disease. Generalized tonic-clonic seizures predominate in both UE and HE, while focal seizures are documented particularly in HE secondary to portosystemic shunting. EEG findings include triphasic waves (OR=8.10 for liver insufficiency), generalized background slowing, and periodic lateralized epileptiform discharges. Cirrhosis was independently associated with status epilepticus (HR=1.9, 95% CI=1.3–2.8) but not isolated seizures. Nonconvulsive status epilepticus carries mortality rates of 37–52% in critically ill metabolic encephalopathy patients. Lentiform fork sign on MRI characterizes uremic encephalopathy seizures with basal ganglia involvement. EEG parameters inversely correlate with ammonia levels, MELD score, and cognitive performance scores in hepatic encephalopathy. Discussion: The pathophysiology of seizures in UE involves NKCC1-mediated depolarization of EGABA secondary to astrocyte potassium buffering failure, NMDA receptor activation by acute ammonia, and retention of multiple uremic toxins. In HE, ammonia-induced astrocytic swelling, GABAergic dysregulation, and peripheral neuroinflammation collectively lower the seizure threshold. Focal seizures in HE are distinctively associated with portosystemic shunting (TIPS), while generalized seizures dominate both conditions. Treatment requires addressing the underlying metabolic derangement alongside judicious antiseizure medication selection, given altered pharmacokinetics in renal and hepatic dysfunction. Conclusion: Seizures in uremic and hepatic metabolic encephalopathy are predominantly generalized tonic-clonic, though focal manifestations occur particularly with portosystemic shunting. EEG—especially triphasic waves—and MRI provide complementary diagnostic information. Mortality is significantly associated with seizure occurrence and nonconvulsive status epilepticus in both conditions. Standardized prospective studies with larger cohorts are urgently needed to establish evidence-based antiseizure medication treatment guidelines specific to these populations.